THE EFFECT OF SCHOOL HOLIDAYS AFTER THE GOVERNMENT PROVIDES SLACK IN THE TOURISM SECTOR ON HOTEL OCCUPANCY RATES IN THE CITY OF BANDUNG, WEST JAVA - Tuti Iriani; Mila karmila; R. Soni Sumali; Jaja Kurnia Santoni; Arman Syah Putra; Nurul Aisyah (Journal of Innovation Research and Knowledge, 2022)
The background of this research is how to find out the school holiday variables, and hotel occupancy rate variables that can significantly influence, Bandung City Jakarta West Java variable with this research it will be known the City of Bandung, can be influenced by any variables so that the City of Bandung can develop into a big city and can become a world tourist destination. The method used in this research is to use quantitative methods, using a survey tool that was conducted on 100 Bandung residents who went on city tours during school holidays. The problem raised in this study is whether there is a relationship between school holidays and hotel occupancy rates for the city of Bandung, West Java. With the problems raised in this study, it will be known what variables can affect a city in developing its tourism. the purpose of this study resulted that the school holiday variable and the hotel occupancy rate variable can affect the Bandung City West Java variable with the school holidays and the hotel variable level can increase so that it can affect tourists in a city, namely the city of Bandung, West Java.